Attitudes to participating in a birth cohort study, views from a multiethnic population: a qualitative study using focus groups. (17th June 2016) - Garg, Neeru; Round, Thomas P.; Daker‐White, Gavin; Bower, Peter; Griffiths, Chris J.
Abstract: Background: Recruitment to birth cohort studies is a challenge. Few studies have addressed the attitudes of women about taking part in birth cohort studies particularly those from ethnic minority groups. Objective: To seek the views of people from diverse ethnic backgrounds about participation in a proposed birth cohort examining the impact of infections. Design and setting: Eight focus groups of pregnant women and mothers of young children took place in GP surgeries and community centres in an ethnically diverse area of east London. Purposeful sampling and language support ensured representation of people from ethnic minority groups. Audio recordings were taken and transcripts were analysed using the Framework approach. Main outcome measures: The views of participants about taking part in the proposed birth cohort study, in particular concerning incentives to taking part, disincentives and attitudes to consenting children. Results: There was more convergence of opinion than divergence across groups. Altruism, perceived health gains of participating and financial rewards were motivating factors for most women. Worries about causing harm to their child, inconvenience, time pressure and blood sample taking as well as a perceived lack of health gains were disincentives to most. Mistrust of researchers did not appear to be a significant barrier. The study indicates that ethnicity and other demographic factors influence attitudes to participation. Conclusions: To recruit better, birth cohort studies should incorporate financial and health gains as rewards for participation, promote the altruistic goals of research, give assurances regarding the safety of the participating children and sensitive data, avoid discomfort and maximize convenience. Ethnicity influences attitudes to participation in many ways, and researchers should explore these factors in their target population.